2012
DOI: 10.1002/joc.3601
|View full text |Cite
|
Sign up to set email alerts
|

Improving spatial temperature estimates by resort to time autoregressive processes

Abstract: Temperature estimation methods usually involve regression followed by kriging of residuals (residual kriging). Despite the performance of such models, there is invariably a residual which is not necessarily unpredictable because it may still be correlated in time. We set out to analyse such residuals through resort to autoregressive processes. It is shown that the optimal period varies depending on whether it is identified by functions of the form res d = f (res d−1 , res d−2 , . . . , res d−p ) or by partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Upon completion of the regression analysis, 325 residuals are obtained for each of the 366 days. Joly et al (2013) have shown that the application of an autoregressive process can reduce these residues. In time series such as daily PM10 concentrations, Neal et al (2014) have demonstrated that the value recorded on any day at each station is dependent on the values recorded the day before.…”
Section: Figure 2 Available Data and Their Transformation For Further...mentioning
confidence: 99%
“…Upon completion of the regression analysis, 325 residuals are obtained for each of the 366 days. Joly et al (2013) have shown that the application of an autoregressive process can reduce these residues. In time series such as daily PM10 concentrations, Neal et al (2014) have demonstrated that the value recorded on any day at each station is dependent on the values recorded the day before.…”
Section: Figure 2 Available Data and Their Transformation For Further...mentioning
confidence: 99%